PRAGMA-SEMIOTICS COMPETENCES IN WULANGREH BOOK (SERAT WULANGREH) - Wuryantoro, Aris (Journal of Islam and Science, 2019)
Abstract. Pragmatics is one of linguistic branches which studies about language in used. On the other hand, Semiotics studies about sign and its use. Javanese has a speech tanggap ing sasmita.  Tanggap ing sasmita is an old word or speech that has been passed down for generations and is still very much needed in today's life, especially in the era of the free market with various kinds of information to communicate. The tanggap ing sasmita amrih lantip was then one of the word in the song of the Wulangreh Book written by Sri Susuhunan Pakubuwana IV (PB IV) which is very phenomenal. The purpose of this paper is to analyze the Serat Wulangreh by Sri Susuhunan Pakubuwana IV, especially in the Kinanti 1 song with a pragmatic and semiotic approach. This paper uses a descriptive qualitative research method. Data obtained by documentation and content analysis. Source of the data was Kinanti song (one of macapat songs) by Sri Susuhunan Pakubuwana IV. Data analyzed by interactive model. The results of the analysis reveals that the speech "tanggap ing sasmita amrih lantip" in Serat Wulangreh is full of utterances which indicate the existence of piwulang (teaching) of pragmatic and semiotic competences both for the speaker and his audience. The speeches referring to pragmatics and semiotics are kalbu, lantip, mangan, nendra, dhahar, guling, and batin.Keywords: tanggap ing sasmita, competence, pragmatics, semiotics